Risk and protection: alcohol use among urban youth within the birth to twenty (BT20) cohort - Ramsoomar, Leane (My University, 2016)
Background: South Africa (SA) faces a formidable threat to public health attributable to alcohol use. The heavy burden of alcohol-attributable morbidity, mortality and social harms borne by SA youth is concerning. In a series of papers, this study examined: current national trends in adolescent alcohol prevalence; the associations of prevalence with alcohol-related mortality; and the implications of the overall findings for alcohol policy in SA. The study also investigated adolescent alcohol use and its determinants at key developmental stages (early and late adolescence), among 1 647 urban adolescents in Soweto, South Africa. Employing a socio-ecological framework, multiple risk and protective factors that determine adolescent alcohol behaviours at late adolescence were empirically tested. Methods: Data originated from seven sources: two national household, (South Africa Demographic and Health Survey-SADHS); two school-based youth risk behaviours surveys (YRBS); and two phases of a mortuary-based sentinel surveillance study. Additionally, a cross-sectional survey of adolescent alcohol use and its determinants was nested within Birth to Twenty (Bt20), a birth cohort study which prospectively follows 3273 children and their mothers from its inception in 1990 to date. Following a review of national data among 13- 19 year olds, bivariate analysis of alcohol use and alcohol-related harm among 13- 19 year olds, and alcohol use and mortality among 15-19 year olds, respectively, pertinent policy implications are discussed. Descriptive statistical analyses examined alcohol prevalence at early (13 years) and late (17/18 years) adolescence in the Bt20 cohort, while bivariate and multivariate analyses determined the associations and predictive values of socio-demographic, individual, and interpersonal factors on adolescent alcohol behaviours. Multi-level generalised linear mixed modelling determined if community level variables explain variability in the likelihood of having engaged in alcohol behaviours at 17/18 years old. Results: Nationally, alcohol use was stable but high among adolescents at 20 - 25% (SADHS) and 49 - 50% (YRBS) over the period 1998-2008. Twelve percent of adolescents initiated alcohol use before age 13. Significant gender differences existed in alcohol consumption, with a predominance of male drinking. Binge drinking increased significantly among females from 1998 to 2003. Homicide, suicide and unintentional deaths among 15- 19 year olds were significantly* associated with positive blood alcohol concentration. Within the Bt20 cohort, lifetime and current alcohol use, and binge drinking, is prevalent, and increases with progression from early to late adolescence. Consistent with national findings, significantly* more males than females engaged in all alcohol behaviours. The frequency of lifetime alcohol use increased from 22% in early adolescence to 66% in late adolescence. Gender, maternal education, and socio-economic status (SES) predicted lifetime alcohol use in early adolescence, while marital status was an additional predictor of the same in late adolescence. In late adolescence, bivariate regression models indicated that alcohol refusal self-efficacy, alcohol expectations, peer influence, household SES, neighbourhood economic level and community level SES were significantly associated with lifetime alcohol use. However, multi-level analyses revealed no direct association between community SES and adolescent alcohol behaviours. Discussion: The high prevalence of lifetime, current alcohol use, and binge drinking, together with early alcohol debut indicates that, alcohol use is a significant public health problem facing SA youth. Adolescent drinking behaviour is the result of a complex interplay between individual, interpersonal and community-related risk and protective determinants. Empirically validated risk and protective factors represent potential points of intervention for prevention and reduction of adolescent drinking. This necessitates multi-faceted responses for prevention on one end of the continuum and harm reduction on the other. Conclusion: Findings challenge current regulatory alcohol policies, the implementation of which falls short of ensuring that minimum drinking age laws are adequately effected. In addition, regulatory policies appear inadequate in ensuring that strategies translate into a reduction in harmful alcohol use by SA youth. Authoritative and consistent implementation of regulatory policies, in addition to harm reduction strategies, is necessary. *p<0.01
Submitted in fulfilment of the requirements for the degree of DOCTOR OF PHILOSOPHY Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2015